(untitled) (Global Journal of Computer Science and Technology, 2025)
Cloud computing has greatly changed how businesses work bringing better scaling and efficiency At the same time this shift has created some security problems in how organizations handle identity and access which is key to keeping businesses secure Old-fashioned identity systems are easy to manage because they let users sign in once to access everything But this setup has a single point of failure making it a target for attackers More and more cyberattacks are aimed at these central identity systems showing problems in how organizations verify identities Identity-related security issues are costing companies money and disrupting their work Blockchain along with the idea of self-sovereign identity gives a good option instead of the usual central systems Decentralized identity systems use identifiers and credentials based on blockchain This gets rid of single points of failure while improving user privacy and control over data This way to check trust is stronger resists attacks and system errors and still follows rules about protecting privacy